Uncover Creative Thinking Skills Development in Accelerated Class: (case study: National plus school in north sulawesi, Indonesia) - Fera L Tampi; Jenny I Dengah; Danny A Masinambow (Jurnal Edusci, 2025)
Background. There were some ideas for accelerating Indonesia’s K-12 education using alternative names to RSBI (Rintisan Sekolah Berbasis Internasional or Prepared International Standard School), which has already been proposed by law, such as accelerated classes or national schools plus. While this class charges a higher rate than the standard class, many parents hope that the English usage in class will accelerate their children's progress. On the other hand, it should develop critical thinking skills for students to differentiate an accelerated class from others. Aims. This research aimed to find evidence and uncover the development of critical thinking skills in an accelerated class. The entire study took place in North Sulawesi, involving 19 schools across K-12 grades (from elementary to high school), and data were collected through observation, interviews, and questionnaires. Methods. This research employs a field study to collect data from entire schools that offer accelerated classes in North Sulawesi. Using the ex post facto method, which involves identifying something that has already occurred, we employed interviews, observation, and document study to gather all the necessary data. As mentioned previously regarding schools as objects, we attempted to delve deeper into these critical thinking skills in students, as well as in the teachers who take responsibility in class. Conclusion. There are some critical key results from it, which are: (1) the assumption of accelerated class, between merely English usage or critical thinking skill, (2) teachers and students wish in creating critical thinking skill outcome from learning process, (3) teacher having difficulties in planning critical thinking skill effort in class, (4) students somehow want critical thinking skill is being held in accelerated class using proper learning process, and (5) good facility and English usage is not enough for accelerated class with such high rate.